Digital Trust, Customer Experience, and Electronic Word of Mouth on Purchase Decision: The Mediating Effect of Customer Satisfaction - Jumai Latte; Ary Yudianto (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
The rapid growth of e-commerce in Indonesia has significantly transformed consumer behavior in digital purchasing activities. In the increasingly competitive digital business environment, companies are required to understand the factors influencing customer satisfaction and purchase decisions. This study aims to analyze the effects of digital trust, customer experience, and E-WOM on customer satisfaction and purchase decisions, as well as to examine the mediating role of customer satisfaction. The research employed a quantitative approach with an explanatory research design. Data were collected through an online questionnaire distributed to 250 active e-commerce users in Indonesia who had completed at least two transactions within the last six months. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.1.1.8 software. The findings reveal that digital trust, customer experience, and E-WOM have positive and significant effects on both customer satisfaction and purchase decisions. Customer experience emerged as the most dominant factor influencing satisfaction and purchasing behavior. Furthermore, customer satisfaction was found to mediate the effects of digital trust, customer experience, and E-WOM on purchase decisions. These findings imply the importance of enhancing platform security, improving customer experience quality, and effectively managing digital reviews to strengthen consumer purchase decisions.